Pembelajaran Aplikatif Pondok Pesantren dan Dampaknya Terhadap kualitas Outcome Siswa (Studi Kasus di Pondok Pesantren Darunnajah, Jakarta) - Nurbaiti Nurbaiti (STAI ALHIKMAH Jakarta, 2017)
Education is the process of humanizing human beings, in other words, education is a humanization process, thus the learning process must be adapted to the human condition. However, there are differences in interpret humanizing human beings, so, resulting the differences in opinion between humanist education according to Islam with humanist education according to western theory. Islam seeshumanizinghumanbeingsbygivingfreedomtohumans as long as it is not contrary to Islam, thus human freedom is not unlimited freedom. This is contrast to the western-based view of humanist education which states that humanist education is education by giving freedom to the students during the learning process. The implication of humanist learning according to Islam which came to be known as humanistic Islamic Education. It is the applicative learning of Islamic Boarding School. Learning with this model, student practice directly about the material that they have learnt. Thus, education is a habit. This means that to improve the quality of outcome needs to be given the education through habituation. The higher level of habituation performed, the higher quality of outcome. The outcomes quality in Islamic Boarding School Darunnajah is quite good. It can be seen that the alumni of Islamic Boarding School Darunnajah are accepted in Gajah Mada University (UGM), Institut Teknologi Bandung (ITB), Institut Pertanian Bogor (IPB) and Institut Agama Islam Negeri (IAIN) Sunan Ampel. Even many of them are continuing their education abroad, such as : Malaysia, Cairo (Egypt), Madinah and England, while with Pakistan, the cooperation is just opened in 2017. Keywords: Islamic boarding school, Islamic humanistic education, Applicative learning, Outcome. Pendidikan merupakan proses memanusiakan manusia, dengan kata lain pendidikan merupakan proses humanisasi, dengan demikian proses pembelajaran harus disesuaikan dengan keadaan manusia. Namun terdapat perbedaan dalam memaknai memanusiakan manusia, sehingga timbul perbedaan pendapat antara pendidikan humanis menurut agama Islam dengan pendidikan humanis menurut teori Barat. Islam memandang memanusiakan manusia adalah dengan memberikan kebebasan kepada manusia selama tidak bertentangan dengan agama Islam, dengan demikian kebebasan manusiabukanlahkebebasantanpabatas. Hal ini berbedadengan pandangan pendidikan humanis versi barat yang menyatakan bahwa pendidikan humanis adalah pendidikan dengan memberikan kebebasan pada siswa selama proses pembelajaran. Implikasi dari pembelajaran humanis menurut Islam yang kemudian dikenal dengan nama Pendidikan Humanistik Islami adalah pembelajaan aplikatif pondok pesantren. Pembelajaran dengan model ini, santri/siswa mempraktekkan langsung tentang materi yang sudah dipelajarinya. Dengan demikian, pendidikan merupakan pembiasaan. Hal ini berarti untuk meningkatkan kualitas outcome maka perlu diberikan pendidikan melalui pembiasaan. Semakin tinggi tingkat pembiasaan yang dilakukan maka semakin tinggi pula kualitas outcome. Kualitas outcome pondok pesantren Darunnajah cukup baik, hal ini bisa dilihat bahwa alumni pondok pesantren Darunnajah diterima di Universitas Gajah Mada (UGM), Institut Teknologi Bandung (ITB), Institut Pertanian Bogor (IPB) dan Institut Agama Islam Negeri (IAIN) Sunan Ampel atas beasiswa dari Departemen Agama. Bahkan banyak diantara mereka yang melanjutkan pendidikan ke luar negeri, yaitu : Malaysia, Kairo (Mesir), Madinah dan Inggris, sedangkan dengan Pakistan baru pada tahun 2017 ini dibuka kerjasama. Kata Kunci: Pondok Pesantren, Pendidikan Humanistik Islam, Pembelajaran Aplikatif, Outcome.